Sensor node placement based on minimax for effective surveillance - Abidin H.Z.; Din N.M. (2023)
Abilities in sensing, storing data, processing data and transmitting data has made Wireless Sensor Networks (WSN) to be applied in providing effective surveillance. Optimum sensor nodes placement in the surveillance area is needed since the number of sensor nodes that can be deployed are limited. The positions of sensor nodes must be able to provide maximum coverage. This paper describes an initial progress of an ongoing project. A sensor nodes placement technique which is based on minimax algorithm is proposed where surveillance locations will be monitored by the closest sensor nodes. Performance study has been carried out by comparing the performance of minimax and ideal value in terms of coverage ratio. Coverage ratio indicates the number of surveillance locations that received effective coverage. Simulation results obtained shows that coverage ratio produced by minimax technique is directly proportional to the number of sensor nodes and can be considered acceptable. 2012 IEEE.